A case of chronic anorexia nervosa with child-bearing by in vitro fertilization necessitating comprehensive team support. (5th December 2014) - Toki, Shigeru; Hashimoto, Eri; Masuda, Masayuki; Machino, Akihiko; Yamawaki, Shigeto
Lesson: Generalists should be aware of the issues surrounding pregnancy in patients with anorexia nervosa and discuss well with patients and their families before in vitro fertilization.